KAJIAN PERIKANAN TANGKAP IKAN JULUNG-JULUNG (Hyporhamphus affinis) DI PERAIRAN KABUPATEN KEPULAUAN SANGIHE - Wuaten, Julius F; Reppie, Emil; Labaro, Ivor L (Sam Ratulangi University, 2011)
ABSTRACTThe objective of this research was to predict maximum sustainable yield of garfish resources in the waters of Sangihe Islands District; to analyze the fishing season of garfish; to map the location of coral reef expected to be a breeding ground of garfish; and to assess the biological, economic, social and environmental aspects of garfish in Sangihe Island district. Garfish maximum sustainable yield was calculated at about 70 tons/year with a maximum effort of 3,613.71 trips. Fishing season of garfish was very dependent on wind direction and speed throughout the year. The percentage of live coral cover at a depth of 5 meters was 56.16-70.17% and a depth of 3 meters was 44.33-83.75%. The ratio of male and female sexes was 35.92-64.07%. Based on length-weight analysis of the garfish growth was classified allometric with a length of 16.7-20.7 cm and weighs between 35-55 g. The financial analysis of garfish fisheries in this area showed that the of Benefit Investment ratio was 1.19 and the Benefit Cost ratio was about 0.94.ABSTRAKTujuan dari penelitian ini adalah untuk memprediksi pemanfaatan maksimum sumberdaya lestari pada ikan julung-julung di perairan Kabupaten Kepulauan Sangihe; untuk menganalisis musim penangkapan ikan tersebut, memetakan lokasi terumbu karang diharapkan dapat menjadi tempat berkembang biak dari julung-julung, serta menilai aspek biologi, ekonomi, sosial dan lingkungan di kabupaten Pulau Sangihe. Pemanfaatan maksimum sumberdaya lestari ikan julung-julung dihitung sekitar 70 ton/tahun dengan upaya maksimal 3.613,71 trip. Musim penangkapan garfish sangat tergantung pada arah dan kecepatan angin sepanjang tahun. Persentase penutupan karang hidup pada kedalaman 5 meter adalah 56,16-70,17% dan kedalaman 3 meter adalah 44,33-83,75%. Rasio jenis kelamin jantan dan betina adalah 35,92-64,07%. Berdasarkan analisis pertumbuhan panjang-berat garfish diklasifikasikan alometrik dengan panjang 16,7-20,7 cm dan berat antara 35-55 g. Hasil analisis keuangan perikanan garfish di Sangihe Kabupaten menunjukkan bahwa rasio Manfaat Investasi adalah 1,19 dan rasio Biaya Manfaat sekitar 0,94.